The effectiveness of promotional mix to create customer awareness towards the existing of business sales TM Melaka in 2007 / Mohd Syamsul Mohd Sutan - Mohd Sutan, Mohd Syamsul (Faculty of Business and Management, 2008)
Business Sales Department or BS is the Subsidiaries Company of Telekom Malaysia Berhad. This department was focusing more on corporate or company sector which includes the business sector, industry sector, financial sector, legal sector and others government sectors. There are many telecommunication companies in the country. They make the greatest effort to attract customers. It also creates competition among them while operating in an increasingly complex business environment. Telekom Malaysia Berhad have done promotional mix such as advertising, publicity, sales promotion and direct selling in order to promote and sell their products to their existing customers and also to new or prospect customers. The main purpose of this study is to determine the level of customers' awareness towards the promotional mix done by TM, identify significant relationship between promotional mix and customer awareness, identify the most effective promotional mix in create customer awareness and also to provide recommendations in improving promotional mix in creating customer awareness.. This research is conducted by using non-probability sampling and the sampling method is convenience sampling. The sampling size would be 80 respondents, taken conveniently at Telekom Business Sales, Melaka customers. From the finding the most effective promotional mix in create customer awareness is advertising. Based on the finding, some recommendations have been suggested in order to help increase customers awareness.